2005
DOI: 10.1111/j.1537-2995.2005.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular potassium concentrations in red blood cell suspensions after irradiation and washing

Abstract: [K(+)e] increases after washing irradiated and nonirradiated packed RBCs. After irradiation and washing, the [K(+)e] for the initial 6 hours can be predicted from the [K(+)e] immediately after washing. There is a low probability that a unit of RBCs would have a [K(+)e] greater than 5 mEq per L during 6 hours of storage at 4 degrees C after washing if the cells are not irradiated and for 3 hours if the cells are irradiated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 27 publications
6
59
0
2
Order By: Relevance
“…On the other hand, the changes between pre and post-irradiation in each group of up to 14 days storage and >14 days storage showed significant changes in the plasma haemoglobin indicates irradiation itself also causes some changes (table-3). This study showed similarity with previous study where free haemoglobin levels were increased in stored irradiated red cell components (Weiskopf et al, 2005) 19 but remain within acceptable limits. Regarding the biochemical values of Na + , K + and LDH, comparison at different storage period of 14 days and >14 days showed significant changes in Na + , K + and LDH which reflects gradual storage changes in both pre and post irradiated samples.…”
Section: Methodssupporting
confidence: 91%
“…On the other hand, the changes between pre and post-irradiation in each group of up to 14 days storage and >14 days storage showed significant changes in the plasma haemoglobin indicates irradiation itself also causes some changes (table-3). This study showed similarity with previous study where free haemoglobin levels were increased in stored irradiated red cell components (Weiskopf et al, 2005) 19 but remain within acceptable limits. Regarding the biochemical values of Na + , K + and LDH, comparison at different storage period of 14 days and >14 days showed significant changes in Na + , K + and LDH which reflects gradual storage changes in both pre and post irradiated samples.…”
Section: Methodssupporting
confidence: 91%
“…This latter rationale has been challenged, particularly when applied to less-than-massive volumes of blood transfused, because when small volumes are transfused, the major consideration for the patient is the total amount of K þ transfused and the transfusion rate. 12,13 During ECMO, the transfusion volume is sufficiently small and the blood is infused sufficiently slow that it probably completely mixes with the patient's blood volume, resulting in little, if any, increase of in vivo plasma K þ levels.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Evidence for such damage includes impaired aggregability, adherence, and deformability, 6 enhanced haemoglobin and glutathione (GSH) oxidation, 7 increased haemolysis and leakage of intracellular potassium, and lactate dehydrogenase. [8][9][10][11] Plant compounds can protect cells against radiationinduced ROS-mediated damage. [12][13][14] Quercetin, 3, 3 ′ , 4 ′ , 5, 7-pentahydroxyflavone, is one of the most abundant dietary polyphenolic substances occurring in fruits and vegetables.…”
Section: Introductionmentioning
confidence: 99%